Risk Prone Litigators: Manifestations of Their Participation in the Civil Procedure - Carrasco Delgado, Nicolás (2024)
This article develops a theoretical framework on the propensity for risk applied to litigation. From this theoretical framework, it follows that the risk prone will initiate legal proceedings more than those averse to it; that when the risk prone are sued, their propensity to risk does not decrease in the face of low variability chance of loss in comparison with previous chances of loss of greater variability; and that furthermore, they generate greater legal expenses than people of other risk profiles. The aforementioned causes greater social losses on increasing the negative externalities of litigation due to the greater divergence between its private and social benefits. The latter shall be examined regarding the issues of permanent courts and the possibility of reaching agreements.